Aspirin and pre‐eclampsia prevention in women with pre‐existing diabetes: a retrospective study. Issue 10 (18th October 2021) - Lah, Siehoon; Cheung, N Wah; Lee, Vincent; Athayde, Neil; Inglis, Emma; Padmanabhan, Suja
Abstract: Background: Aspirin is routinely prescribed in high‐risk pregnancies to prevent pre‐eclampsia; however, there is a paucity of data in women with pre‐existing diabetes. Aims: To assess the efficacy and safety of aspirin in women with pre‐existing diabetes in preventing pre‐eclampsia. Methods: A retrospective review of women with pre‐existing diabetes who attended antenatal clinics in a tertiary referral hospital between 2013 and 2019 was conducted. Cases were those receiving aspirin prior to 16 weeks, with pre‐eclampsia as the primary outcome. The relationship between early pregnancy glycaemic control and pre‐eclampsia was also assessed. Results: Of the 164 women included in the study, 45 received aspirin. There were no differences in pre‐eclampsia (odds ratio (OR) 0.9 (0.3–3.0), P = 0.924) or any other measure of placental insufficiency (OR 1.7 (0.7–4.3), P = 0.243) between the aspirin and control groups after adjusting for baseline differences. Aspirin therapy was associated with an increased risk of postpartum haemorrhage (PPH) (OR 3.1 (1.1–9.1), P = 0.041). The incidence of pre‐eclampsia increased stepwise according to early pregnancy HbA1c subgroups of ≤6.0% ( n = 47), 6.1–7.5% ( n = 57) and > 7.5% ( n = 39), with rates of 0, 12.3 and 20.5% ( P = 0.007) respectively. Conclusions: The aspirin group had a higher baseline risk of pre‐eclampsia and placental insufficiency, therefore the absence of difference between the groups favoured the efficacy of aspirin. PPH was highlighted as a potential complication of therapy, and early pregnancy HbA1c as a novel risk stratification tool for pre‐eclampsia in women with pre‐existing diabetes.